Emerging market firms and dual business models: An Indian perspective - Swarup Kumar Dutta (Journal of Business Models (JOBM), 2022)
Managers in organizations face severe challenges and conflicts that arise from pursuing dual business models. Documented studies are available on how Western Multinationals operate in emerging markets, however, little evidence is available about how home-grown emerging market firms pursue this challenge in their home markets. With an ambidexterity perspective and activity systems approach, this study aims to offer novel insights into how Indian firms carry out organizational integration and separation-they focus on domains of expertise in organizational activities such as sales and marketing rather than on business units-as they pursue the challenges of dual business models, in contrast to the multinational corporation (MNC) approach.
Keywords: 650